Pengukuran Kinerja Pegawai Tata Usaha Berbasis Key Performance Indicator Pada Direktorat Kelaikudaraan Dan Pengoperasian Pesawat Udara: Employee Performance Measurement Based on Key Performance Indicators at the Directorate of Airworthiness and Aircraft Operations - Feri Firman; Tri Lestari (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
That the quality of employee performance in each agency is the heart to determine whether or not the wheels of the organization run, so in this study aims to measure the extent to which the level of performance of employees of the DKPPU Office Administration Section to be able to periodically evaluate employees so that they can carry out their duties as well as possible. The method used in studying the performance of employees of the DKPPU Office Administration Section uses a non-statistical quantitative research method, namely a research approach that uses numerical analysis and statistical data, but because it is non-statistical, it still uses descriptive analysis on one research variable, namely performance based on key performance indicators with indicators as a tool in measuring the level of employee performance based on Permenpan 6 of 2022. The purpose of this study is to measure the level of employee performance in the DKPPU Office Administration Section as well as material for evaluating employee performance improvements. From the results of the study there are two indicators used, namely the main work results and work behavior, based on the measurement results, the main work results score is 8.88 and work behavior is 8.54 and the total score is 8.71 after being converted into a work predicate, the results of the DKPPU Office Administration employee performance measurement have a Good work predicate.